Towards the Eye of the Human Storm - Mesquida Sampol, Joan (Razón y fe, 2020)
Most of the analyses about the present secularization and the withdrawal of traditional forms of religiosity do not always run parallel with concrete proposals of how to face the challenge of the Church in departure proposed by the Pope. This work argues that the fundamental axes of that mission must be sought in the special role of the laity, the centrality of the Gospel message and the search for closeness to people who, even without knowing it, long to meet God.